Biaxial flexural strength of Turkom-Cera core compared to two other all-ceramic systems - Bandar Mohammed Abdullah Al-Makramani; Abdul Aziz Abdul Razak; Mohamed Ibrahim Abu-Hassan (University of São Paulo, 2010)
Advances in all-ceramic systems have established predictable means of providing metal-free aesthetic and biocompatible materials. These materials must have sufficient strength to be a practical treatment alternative for the fabrication of crowns and fixed partial dentures. OBJECTIVES: The aim of this study was to compare the biaxial flexural strength of three core ceramic materials. MATERIAL AND METHODS: Three groups of 10 disc-shaped specimens (16 mm diameter x 1.2 mm thickness - in accordance with ISO-6872, 1995) were made from the following ceramic materials: Turkom-Cera Fused Alumina [(Turkom-Ceramic (M) Sdn Bhd, Puchong, Selangor, Malaysia)], In-Ceram (Vita Zahnfabrik, Bad Säckingen, Baden-Württemberg, Germany) and Vitadur-N (Vita Zahnfabrik, Bad Säckingen, Baden-Württemberg, Germany), which were sintered according to the manufacturer's recommendations. The specimens were subjected to biaxial flexural strength test in an universal testing machine at a crosshead speed of 0.5 mm/min. The definitive fracture load was recorded for each specimen and the biaxial flexural strength was calculated from an equation in accordance with ISO-6872. RESULTS: The mean biaxial flexural strength values were: Turkom-Cera: 506.8±87.01 MPa, In-Ceram: 347.4±28.83 MPa and Vitadur-N: 128.7±12.72 MPa. The results were analyzed by the Levene's test and Dunnett's T3 post-hoc test (SPSS software V11.5.0 for Windows, SPSS, Chicago, IL, USA ) at a preset significance level of 5% because of unequal group variances (P<0.001). There was statistically significant difference between the three core ceramics (P<0.05). Turkom-Cera showed the highest biaxial flexural strength, followed by In-Ceram and Vitadur-N. CONCLUSIONS: Turkom-Cera core had significantly higher flexural strength than In-Ceram and Vitadur-N ceramic core materials.